Sarcoidosis: Internal medicine perspective - Mehtap Tınazlı; Gaukhar Bakhtiyarova (National Scientific Medical Center, 2016)
Sarcoidosis is a systemic autoimmune disease characterized by noncaseatinggranulomatous inflammation with unknown etiology.Although the lungs and respiratory system are most commonlyinvolved, sarcoidosis may involve virtually any part of the body,including the locomotor system, eyes, skin, lymph nodes. Diagnosis attained via consensus between the clinical presentation and natural history, pattern of major organ involvement, confirmatory biopsy, and response to therapy. Histopathological features remain the gold standard in diagnosis. Radiologic staging in sarcoidosis is based on the chest X-ray. If chest radiographis normal, high-resolution computed tomography (HRCT) can demonstrate pathological changes in a detailed manner. Sarcoidosis generally follows a benign course with occasional spontan remissions. The most important causes of mortality are acute and chronic respiratory failure, pulmonary hypertension and hemoptysis due to aspergillosis. When treatment is indicated, glucocorticoids remain the only recognized effective therapy for active sarcoidosis. Level of evidence for management of sarcoidosis is low, generally reflecting the results of limited number of clinical studies, case series and expert opinion. In selected cases, biological agents including, tumour necrosis factor inhibitors, seem to be promising.